The Private Sector and Youth Skills and Employment Programs in Low and Middle-Income Countries - Glick, Peter J.; Huang, Crystal; Mejia, Nelly (World Bank, Washington, DC, 2015)
Getting youth into productive employment is an urgent policy issue for countries around the world. Many governments in low and middle-income countries are actively engaged in policies to help youth attain the skills they need to do well in work and in life, as well as to find suitable employment. The involvement of the private sector in youth skills development and employment is a complex issue because the nature of the firms and their motivations vary significantly. Multinational corporations operating in low and middle-income countries may be motivated by direct productivity or profit objectives - to secure a skilled workforce, or reliable suppliers - but also, or even primarily, by corporate social responsibility (CSR) factors. Firms that supply training or employment services will be driven by profit considerations when entering these markets and deciding what services to offer and to whom. The purpose of this paper is threefold: (1) to provide a comprehensive look at the way the private sector is involved in youth skills and employment in low- and middle-income countries, considering the broad range of program types and firm types; (2) to present and interpret the available evidence of the effectiveness of this involvement; and (3) to understand where the private sector has been most effective at promoting young people’s labor market success, and what can be done to enhance the role of the private sector to achieve this objective. The report is organized as follows: chapter one gives introduction. Chapter two provides background to the analysis of the private sector role in youth employment in low- and middle-income countries. In chapter three the authors characterize the private sector’s role more systematically using the youth employment inventory, a global database of interventions that are designed to integrate young people into the labor market. Chapter four reviews the evidence of effectiveness of youth interventions involving the private sector. Chapter five briefly draws together strands from the previous review, as well as from the broader literature, to gain an understanding of the institutional and other factors leading to (and in other cases preventing) successful public-private partnerships for youth employment. Chapter six summarizes the main findings of this review, and is followed by a discussion of key gaps in knowledge on the role of the private sector in different types of youth employment intervention that future research should attempt to address, and a review of the main lessons for policy and programming emerging from the study.